(untitled) (Research, Society and Development, 2021)
Sickle cell anemia is a genetic disease, transmitted by an autosomal recessive inheritance, represented by the existence of sickle-shaped erythrocytes, and highly prevalent in Brazil. Carriers of this pathology are asymptomatic in the first six months of life. Early diagnosis is achieved through neonatal screening, allowing the monitoring of patients before the manifestations and symptoms and, with this, the prevention of possible sequelae and complications. This study was carried out through a qualitative and quantitative bibliographic research, aiming to demonstrate, point out and correlate the main characteristics of this pathology with early diagnosis. Highlighting the main points of articles related to sickle cell anemia and its complications, using national and international publications, from the databases: SCIELO (Scientific Electronic Library Online), PubMed, Academic Google and VHL, in which 21 works were part of the construction of the results. Among these, 4 were found on PubMed, 9 on Sciello,7 on Google Scholar and 1 on the BVS platform. Responding to the objectives described, we can conclude that early diagnosis is essential, as the sooner sickle cell anemia is detected, there is more chance that the patient’s quality and life expectancy will increase, with that the neonatal screening plays a fundamental role in this detection.